We demand work! 'Dispossession', patronage and village labour in Bibiyana, Bangladesh. Issue 7 (10th November 2018) - Gardner, Katy
ABSTRACT: This paper critically appraises the usefulness of idioms and theories of 'dispossession' to describe changes taking place in rural Bangladesh, where rapid industrialization and 'development' have led to profound shifts in the agrarian economy. On the basis of long-term fieldwork in north-eastern Bangladesh, where the multinational company Chevron operate a large gas field, I argue that rather than political and economic struggles in the area involving access to land, it is access to work which is now all important for livelihoods and, as such, has become the basis for local patronage and political power. Theories of 'accumulation by dispossession', still widely cited in the anthropology of neo-liberal development in South Asia, are thus of limited help in explaining the changes and continuities which animate local political and economic struggles.